Self-study, obtaining or viewing terrorist material over the internet : a legitimacy test of consumer-oriented criminal law provisions in four Western-European countries - De Coensel, Stéphanie (2020)
The internet is a key source of information, communication and propaganda in the context of terrorism. Policymakers increasingly resort to measures that monitor, control and punish internet-related activity. One type of measures concerns the criminalisation of consumers of certain terrorist material over the internet, ranging from self-study over more specific autonomous provisions. This contribution aims to subject this criminal law approach to a legitimacy test, studying the minimum standards of the European Union, as well as the legal framework of four Western-European countries (i.e. Belgium, the Netherlands, France and the United Kingdom). This critical-legal analysis consists of a remote harm analysis, a human rights assessment and a necessity argument. It is argued that the expansion of the scope of criminal liability to a pre-crime era conflicts with certain premises of criminal law and human rights law